2010
DOI: 10.1021/jf100936x
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Postharvest Carbon Dioxide Treatments Induce Selective Molecular and Metabolic Changes in Grape Berries

Abstract: Detached wine grapes ( Vitis vinifera cv. 'Trebbiano', white skinned) were treated for 3 days with 30 kPa of CO(2) and then transferred to air for an additional 9 days to partially dehydrate (about 20% weight loss). At the end of the CO(2) treatment on withering berries, total polyphenols and flavonoids were maintained in the skin, but to a more limited extent in the pulp. An induction of the proanthocyanidin synthesis appeared to be one of the responses to the treatment because both (+)-catechin and (-)-epica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 50 publications
2
31
1
Order By: Relevance
“…The soluble solids content also differed among the cultivars, with the Oseleta berries showing more effective sugar concentration during dehydration than the others, possibly reflecting the smaller berry size and lower juice content. The titratable acidity of Corvina berries increased consistently, whereas there was an initial loss of acidity in the other cultivars in agreement with previous reports (Vicens et al 2009, Becatti et al 2010. The reduction in titratable acidity is largely due to the respiration of malic acid but is counterbalanced by juice concentration due to water loss.…”
Section: Discussionsupporting
confidence: 91%
“…The soluble solids content also differed among the cultivars, with the Oseleta berries showing more effective sugar concentration during dehydration than the others, possibly reflecting the smaller berry size and lower juice content. The titratable acidity of Corvina berries increased consistently, whereas there was an initial loss of acidity in the other cultivars in agreement with previous reports (Vicens et al 2009, Becatti et al 2010. The reduction in titratable acidity is largely due to the respiration of malic acid but is counterbalanced by juice concentration due to water loss.…”
Section: Discussionsupporting
confidence: 91%
“…With reference to gene expression, we observed a down-regulation of VvNCED1 15 transcript levels produced by both, low temperature and high CO 2 levels in rachis and skin, so we cannot establish a link with rachis deterioration, but rather with a more general response. Becatti et al, (2010) also observed a down-regulation of NCED in the skin of wine grapes treated with high CO 2 levels. Conversely, our results showed that 3 days of storage at 0 ºC induced a sharp increase in NCED1 accumulation in pulp, whereas high CO 2 levels clearly 20 restrained this induction.…”
Section: Discussion 10mentioning
confidence: 68%
“…On the one hand, it is known that CO 2 is an essential cofactor for ACO (Dong et al, 1992;Escribano et al, 1996), and it has been shown to induce ethylene production by enhancing ACS activity and synthesis (reviewed by Mathooko, 1996). In this sense, Becatti et al, (2010) observed that 25 high CO 2 applied to detached wine grapes for 3 days at 20 ºC induced ACO and an ACS-like gene expression in skin and pulp. On the other hand, elevated levels of CO 2 can reduce ethylene biosynthesis mainly by inhibiting ACS gene expression and affecting ACO action (de Wild et al, 2003).…”
Section: Discussion 10mentioning
confidence: 99%
“…Cold stress in blood oranges induced transcriptomic modifications directed towards increased flavonoid biosynthesis [52]. Similarly, postharvest carbon dioxide treatments induced proanthocyanidin synthesis in grapes [53].…”
Section: The Use Of Elicitorsmentioning
confidence: 99%